Best in show [videorecording (DVD)] - Guest, Christopher; Levy, Eugene, 1946-; Coolidge, Jennifer; McKean, Michael; O'Hara, Catherine; Posey, Parker, 1968-; Willard, Fred, 1939-2020- (Warner Home Video, 2001)
A comic look at dog show participants (and the pooches who love them).